Reliability of In Vitro Methods Used to Measure Intrinsic Clearance of Hydrophobic Organic Chemicals by Rainbow Trout: Results of an International Ring Trial. (14th May 2018) - Nichols, John; Fay, Kellie; Bernhard, Mary Jo; Bischof, Ina; Davis, John; Halder, Marlies; Hu, Jing; Johanning, Karla; Laue, Heike; Nabb, Diane; Schlechtriem, Christian; Segner, Helmut; et al.
Abstract: In vitro assays are widely employed to obtain intrinsic clearance estimates used in toxicokinetic modeling efforts. However, the reliability of these methods is seldom reported. Here we describe the results of an international ring trial designed to evaluate two in vitro assays used to measure intrinsic clearance in rainbow trout. An important application of these assays is to predict the effect of biotransformation on chemical bioaccumulation. Six laboratories performed substrate depletion experiments with cyclohexyl salicylate, fenthion, 4- n -nonylphenol, deltamethrin, methoxychlor, and pyrene using cryopreserved hepatocytes and liver S9 fractions from trout. Variability within and among laboratories was characterized as the percent coefficient of variation (CV) in measured in vitro intrinsic clearance rates (CLIN VITRO, INT ; ml/h/mg protein or 10 6 cells) for each chemical and test system. Mean intralaboratory CVs for each test chemical averaged 18.9% for hepatocytes and 14.1% for S9 fractions, whereas interlaboratory CVs (all chemicals and all tests) averaged 30.1% for hepatocytes and 22.4% for S9 fractions. When CLIN VITRO, INT values were extrapolated to in vivo intrinsic clearance estimates (CLIN VIVO, INT ; l/d/kg fish), both assays yielded similar levels of activity (<4-fold difference for all chemicals). Hepatic clearance rates (CLH ; l/d/kg fish) calculated using data from both assays exhibited even better agreement. These findings show that both assays are highly reliable and suggest that either may be used to inform chemical bioaccumulation assessments for fish. This study highlights several issues related to the demonstration of assay reliability and may provide a template for evaluating other in vitro biotransformation assays.